DIAGNOSTIC TECHNIQUES FOR THE EARLY DETECTION OF DEGENERATIVE JOINT DISEASES IN CHILDREN - N.I. Taibulatov; L.S. Namazova-Baranova; O.A. Malakhov; N.V. Osipova; A.P. Stepanchenko (Union of pediatricians of Russia, 2010)
The article presents data on modern techniques for the early identification of degenerative disease of joints in children. 120 adolescents aged 12 to 18 years were examined. All the patients were divided into two groups. The main group included 70 children with various manifestations of osteoarthritis. The control group was made up of 50 healthy children with growing pains. The examination helped determine the diagnostic value of various (X-ray, ultrasonic, magnetic resonance) techniques for the study of joints in children with clinical manifestations of osteoarthritis. Key words: children, osteoarthritis, arthralgia, diagnostics. (Pediatric Pharmacology. - 2010; 7(2):66-72)